Rapid Application Development Dalam Pengembangan Sistem Informasi Kesiswaan Berbasis Website (Studi Kasus: Sman 11 Pekanbaru) - Syaliman, Khairul Umam; Ramdani Hadi Nst, Andika (JURNAL FASILKOM, 2024)
This research identifies problems in the student data management process at SMAN 11 Pekanbaru, which still relies on manual recording for students who violate school regulations and students who excel. This causes limitations in operational efficiency. Apart from that, extracurricular activities also experience problems in organizing because the member registration process still uses paper forms. This research aims to develop and analyze a web-based student information system to increase the efficiency and effectiveness of student data management. The system development method used is Rapid Application Development (RAD), this method was chosen because of its flexibility in accommodating the needs of SMAN 11 Pekanbaru with a short implementation time. This system was developed using the PHP and MySQL programming languages as a database management system. System testing is carried out using User Acceptance Testing which involves admin, student affairs, school principals, homeroom teachers, and students as actors in the system. The results of website functionality testing using the Blackbox Testing method are in the good category, with 24 use cases successfully carried out with a success rate of 62.5%. Usability testing shows a high level of agreement with the system built, with a score of 82.4% for the system aspect, 81.8% for the user aspect, and 80% for the interaction aspect.